Latino/a Farmworkers' Concerns about Safety and Health in the Pennsylvania Mushroom Industry. Issue 2 (3rd April 2022) - Sexsmith, Kathleen; Palacios, Effie E.; Gorgo-Gourovitch, Maria; Huerta Arredondo, Ilse A.
ABSTRACT: The purposes of this study were to analyze Latino/a immigrant mushroom workers' perceptions of how the workplace environment shapes occupational safety and health, examine whether and how those perceptions differ by gender, and identify future areas for research on occupational safety and health in the mushroom industry. Researchers conducted structured interviews with 15 women and 45 men on 6 Pennsylvania mushroom farms to obtain their descriptions and perspectives of safety and health risk factors in their workplaces. Approximately one third of respondents had suffered an injury at work, and nearly half felt that there are workplace factors that affect their health and safety. The study found that Latino/a mushroom farmworkers perceive risks that are posed by the indoor infrastructure of mushroom production houses, including poorly maintained wooden walkways and cool indoor temperatures, and by the organization of mushroom production work, including the application of chemicals including pesticides, physical demands of the job, use of small knives, contact with compost, and the piece rate payment system. Workers commonly discussed back pain and believed it was associated with the organization of work. Women in the sample were more likely to be concerned about slips and falls than men and less likely to be concerned about aches and pains. Mushroom farm infrastructure and the specific demands of the jobs pose occupational safety and health risks to Latino/a farmworkers that merit further study to develop adequate public health interventions. Future research should obtain gender-disaggregated objective reports of injury, aches and pains, and discomfort and test for relationships between these reports and the indoor infrastructure and conditions of mushroom production work.